EARLY / OCCULT EHPVO NO LONGER IDIOPATHIC- UNRAVELLING METABOLIC CLUES IN A PROSPECTIVE STUDY IN ASIAN SCENERIO. - Zeeshan Ahmad Wani; Rameez Raja Najar; Asif Iqbal; Afrah Nasir; Muzamil Majeed (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Extrahepatic portal vein obstruction (EHPVO), characterized by occlusion and cavernomatous transformation of the portal vein resulting in portal hypertension. The clinical aspect of EHPVO is well established however its association with metabolic syndrome in adults has not been extensively studied. This study aims to explore the prevalence and components of metabolic syndrome in adult patients diagnosed with occult EHPVO. Aims and Methods: In this prospective observational study conducted in a tertiary care center in Kashmir, India, 109 adult patients aged 15–75 years with non-cirrhotic, non-malignant EHPVO confirmed by abdominal ultrasonography were evaluated. Metabolic parameters such as body mass index (BMI), hypertension, diabetes or pre-diabetes, dyslipidemia, and hyperuricemia. Clinicoetiological evaluation along with follow-up outcomes, were recorded and analyzed. Statistical analysis was performed using SPSS. Categorical variables were expressed as frequencies and percentages and associations were assessed using the Chi-square test. Results: Of the 109 patients, 56 (51.4%) were males and 53 (48.6%) females. Median age was 40.25 years . Metabolic evaluation showed normal BMI ,dyslipidemia, pre-diabetes, hypertension, hyperuricemia in 78.9%, 27.5%, 14.7%, 30.3% and 11% respectively. Eighty percent (80%) were idiopathic, with substantial proportion of these patients displayed features of metabolic syndrome, suggesting a potential link between endothelial dysfunction and EHPVO. Conclusion: This study highlights increased prevalence of metabolic syndrome in early occult EHPVO in Asian population thereby challenges the notion of idiopathic adult EHPVO. This condition however demonstrated a relatively benign course, with no mortality reported during the study’s follow-up period.